Hadis dan Ushul Fiqh: Studi Tentang Peran Hadis dalam Menentukan Hukum Islam - Ola Alifiyanti Zahra Purnama; Sulistiani Sulistiani; Mamay Humaeroh; Hafidz Taqiyuddin (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
In this study discusses the role of Hadith as the second source of Islamic law after the Qur'an, which serves as a guide to life in explaining and detailing Islamic laws. The author uses a qualitative approach to literature studies, collecting information from various books and relevant journals. The discussion covers the understanding of Hadith, its types, and its relationship with the Qur'an, including the challenges in understanding Hadith in the modern era. The results of this study show that Hadith is important in explaining the verses of the Qur'an that are general in nature and become the basis in the process of ijtihad. Conclusion in this study a deep understanding of the Hadith is very important for Muslims to run the teachings according to the guidance of the Prophet Muhammad.